Target and suspect screening of 4777 per- and polyfluoroalkyl substances (PFAS) in river water, wastewater, groundwater and biota samples in the Danube River Basin - Ng, Kelsey; Alygizakis, Nikiforos; Androulakakis, Andreas; Galani, Aikaterini; Aalizadeh, Reza; Thomaidis, Nikolaos S; Slobodnik, Jaroslav (Journal of hazardous materials, 2022)
Per- and polyfluoroalkyl substances (PFAS) are under regulatory scrutiny since some of them are persistent, bioaccumulative, and toxic. The occurrence of 4777 PFAS was investigated in the Danube River Basin (DRB; 11 countries) using target and suspect screening. Target screening involved investigation of PFAS with 56 commercially available reference standards. Suspect screening covered 4777 PFAS retrieved from the NORMAN Substance Database, including all individual PFAS lists submitted to the NORMAN Suspect List Exchange Database. Mass spectrometry fragmentation patterns and retention time index predictions of the studied PFAS were established for their screening by liquid chromatography - high resolution mass spectrometry using NORMAN Digital Sample Freezing Platform (DSFP). In total, 82 PFAS were detected in the studied 95 samples of river water, wastewater, groundwater, biota and sediments. Suspect screening detected 72 PFAS that were missed by target screening. Predicted no effect concentrations (PNECs) were derived for each PFAS via a quantitative structure-toxicity relationship (QSTR)-based approach and used for assessment of their environmental risk. Risk characterization revealed 18 PFAS of environmental concern in at least one matrix. The presence of PFAS in all studied environmental compartments across the DRB indicates a potentially large-scale migration of PFAS in Europe, which might require their further systematic regulatory monitoring.
Keywords: chemické látky znečišťující vodu; Fluorocarbons; Ecotoxicological risk assessment; Per-and polyfluoroalkyl substances (PFAS); voda; řeky; odpadní voda; Water Pollutants, Chemical; Waste Water; společenstvo; Rivers; Water; Danube River Basin; Environmental risk assessment; podzemní voda; Target screening; Groundwater; fluorokarbony; Biota; Suspect screening; Wastewater